THE EFFECT OF SECURITY, TRUST, PERCIEVED USEFULNESS AND PERCEIVED EASE OF USE TOWARDS PURCHASE DECISION IN ONLINE MARKETPLACE SITE TOKOPEDIA.COM (Study of Tokopedia.com users in Malang City) - Kusuma, Zammy Haryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to examine the importance of security, trust, perceived usefulness and perceived usability factor for customer buying decisions from Tokopedia.com. In this study, the population used were tokopedia.com (toppers) users in Malang City. The sample used is Tokopedia.com users (toppers) in Malang City who made more than once online purchases at Tokopedia.com using the Purposive sampling method and took as many as 100 respondents. Multiple Linear Regression is used as a technique for analyzing the data in this study. Hypothesis testing is applied in this study with F test, t test, correlation coefficient, determination coefficient. The classic assumption test in this study was applied using multicollinearity test, heteroscedasticity test, and normality test. The results of this study indicate that the factor of trust, security and perceived usefulness has a very significant impact on purchase decisions, but does not directly affect the perceived ease of use factor significantly Keywords: Security, Trust, Usefulness, Ease of Use, Online Purchase, Purchase Decision